Social Media Marketing: Its Impact on Consumer Decision-Making - Seereddi, Shravya (AG Volumes, 2024)
Buyers and sellers may communicate, exchange comments, and learn about the latest market trends via social media marketing, which is an engaging and dynamic platform. Knowing that social media can be used as a marketing tool, consumers primarily utilise it to save time, purchase everything they need at any time, and help seller’s market their products more effectively by analysing their preferences and utilising a variety of analytical tools. Examine the research on how social media marketing influences consumers’ choices in this comprehensive overview article. It concluded that social media marketing (SMM) plays a vital role in shaping consumer decision-making by leveraging authenticity, transparency, and emotional resonance. It serves as electronic word-of-mouth, simplifying and enhancing purchasing decisions. Businesses use platforms like Facebook and Instagram to engage audiences, build trust, and strengthen brand loyalty. However, research gaps remain in understanding psychological influences and non-Western consumer behavior. SMM strategies that are effective include data-driven marketing decisions, user-generated content, and influencer collaborations. Social media also facilitates grievance redressal, fostering stronger brand-consumer relationships. By continuously adapting, businesses can maximize SMM’s impact, ensuring long-term customer engagement and competitive advantage in the evolving digital landscape.